Body Image Disorders: Comparison between Unilateral Hemisphere Damage and Schizophrenia - J. Cutting (Behavioural Neurology)
The records of a consecutive series of 100 schizophrenics were examined for any mention of body image disorders. These were present in 45 patients, the most common varieties being anomalous bodily experiences. The pattern of these was then compared with the sorts of body image disorders which occur in patients with left hemisphere lesions and in those with right hemisphere lesions. Schizophrenic body image disorders resembled those seen with right-sided lesions much more than they did those occurring following left-sided damage. This result is discussed in relationship to theories of hemisphere imbalance in schizophrenia.